2019
DOI: 10.1186/s12940-019-0544-9
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and mortality in a large, representative U.S. cohort: multiple-pollutant analyses, and spatial and temporal decompositions

Abstract: BackgroundCohort studies have documented associations between fine particulate matter air pollution (PM2.5) and mortality risk. However, there remains uncertainty regarding the contribution of co-pollutants and the stability of pollution-mortality associations in models that include multiple air pollutants. Furthermore, it is unclear whether the PM2.5-mortality relationship varies spatially, when exposures are decomposed according to scale of spatial variability, or temporally, when effect estimates are allowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 28 publications
1
28
1
Order By: Relevance
“…Given that the data used in this study are self-reported, recall bias may exist. Also, air pollution has been discovered to produce a significant effect on health outcome, 46 but we cannot control for it with these data. Therefore future studies should control for this factor.…”
Section: Discussionmentioning
confidence: 95%
“…Given that the data used in this study are self-reported, recall bias may exist. Also, air pollution has been discovered to produce a significant effect on health outcome, 46 but we cannot control for it with these data. Therefore future studies should control for this factor.…”
Section: Discussionmentioning
confidence: 95%
“…To account for temporal variability in pollution exposure, and to evaluate the sensitivity of the proportional hazards assumption relative to its impact on the PM 2.5 -mortality hazard ratio estimates ( 37 ), a temporally decomposed analysis that allowed for time-varying exposure was performed as documented elsewhere ( 38 ). Briefly, the primary cohort was temporally decomposed into 17 yearly cohorts (2000-2016).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, several studies have provided substantial evidence of a positive association between air pollution and cardiovascular disease (CVD), morbidity, and mortality [1][2][3][4][5][6][7][8][9]. In 2015, ambient fine particulate matter (PM 2.5 ) was ranked among the top five mortality risk factors worldwide [4].…”
Section: Introductionmentioning
confidence: 99%